Regulating the PI3K and AMPK pathway: the secret of 1-deoxynojirimycin's success in alleviating chronic diseases - Chengwei Yu; Qirui Hu (Journal of Future Foods)
Abstracts: The chronic diseases (e.g. diabetes mellitus, obesity, and cardiovascular diseases) have become a global public health issue with its increasing morbidity and mortality. However, the effects of drug treatments are limited unless the diet or living habit are monitored and controlled. The traditional Chinese medicine has advantages in treatment of chronic diseases because it can be utilized as both drug intervention and diet intervention. Mulberry leaf is a type of traditional Chinese medicine which possesses hpyerglycemic, anti-obesity, anti-inflammatory and anti-oxidative activities. Therefore, mulberry leaves are widely used to treat chronic diseases. The 1-deoxynojirimycin (DNJ) is the unique alkaloid and the primary component for hypoglycemic effects in the mulberry leaves. Meanwhile, DNJ has also been proved to exert anti-obesity, anti-cardiovascular diseases and anti-cancer effects. However, the underlying mechanisms are unclear yet, which hinders the applications of DNJ in clinic and food industry. Therefore, here we summarized the understanding of the molecular mechanisms underlying the effects of DNJ on the chronic diseases, proposed the key molecular mediators (phosphatidylinositol 3-kinase (PI3K) and adenosine 5′-monophosphate-activated protein kinase (AMPK)) and discussed the future directions to promote the application of DNJ.